Handheld transabdominal ultrasound, after limited training, may confirm first trimester viable intrauterine pregnancy: a prospective cohort study - Judith Krossøy Pedersen; Cecilie Sira; Jone Trovik (Taylor & Francis Group, 2021)
Objectives Handheld point-of-care abdominal ultrasound (POCUS) may be used by primary care physicians while vaginal ultrasound is limited to use in specialist care. We aimed to compare abdominal handheld ultrasound to vaginal ultrasound in determining first trimester viable intrauterine pregnancy and estimate gestational length. Design Prospective cohort study. Setting Gynaecologic outpatient clinic; women referred from GPs during early pregnancy. Handheld ultrasound using VscanExtend® was performed by fourth-year medical students with limited training. Transvaginal ultrasound using high-end devices was performed by ordinary hospital staff. Subjects Women in the first trimester of pregnancy referred for termination of pregnancy or with symptoms of early pregnancy complications. Main outcome measures Rate of confirming vital intrauterine pregnancy (visualizing foetal heart beats) and measurement of crown-rump length (CRL) using handheld abdominal versus vaginal ultrasound. Results In all 100 women were included; 86 confirmed as viable intrauterine pregnancies and 14 pathological pregnancies (miscarriages/extrauterine pregnancies). Handheld abdominal ultrasound detected fetal heartbeats in 63/86 (73% sensitivity) of healthy pregnancies and confirmed lack of fetal heartbeats in all pathological pregnancies, total positive predictive value (PPV) 100% and total negative predictive value (NPV) 38%. From gestational week 7, handheld abdominal ultrasound confirmed vitality in 51/54 patients: PPV 100% and NPV 79%. CRL (n = 62) was median 1 mm shorter (95% confidence interval 1-2 mm) measured by handheld abdominal versus vaginal ultrasound. Conclusion Handheld ultrasound has an excellent prediction confirming viable intrauterine pregnancy from gestational week 7. Validation studies are needed to confirm whether the method is suitable in primary care assessing early pregnancy complications.KEY POINTS When early pregnancy vitality needs to be confirmed, women will traditionally be referred to secondary care for transvaginal comprehensive ultrasonography performed with high-end devices by imaging specialists. In this study personnel with limited former training (fourth-year medical students) performed transabdominal POCUS using a handheld device, investigating 100 first trimester pregnancies for confirmation of viability. Using handheld ultrasound viable pregnancy was confirmed from gestational week 7 with 79% positive and 100% negative predictive value. If handheld ultrasound used in primary care confirms vital intrauterine pregnancy, the need for specialist referral could be reduced.